1993
DOI: 10.1093/intimm/5.6.647
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin gene rearrangement in B cell deficient mice generated by targeted deletion of the JH locus

Abstract: B lymphocyte differentiation is characterized by an ordered series of Ig gene assembly and expression events. In the majority of normal B cells, assembly and expression of Ig heavy (H) chain genes precedes that of light (L) chain genes. To determine the role of the Ig heavy chain protein in B cell development and L chain gene rearrangement, we have generated mice that cannot assemble Ig H chain genes as a result of targeted deletion of the JH gene segments in embryonic stem cells. Mice homozygous for this dele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
253
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 370 publications
(266 citation statements)
references
References 0 publications
12
253
1
Order By: Relevance
“…To confirm the generality of this finding, we extended this analysis to the TS1 transgenic model and developed a line of B cell-deficient TS1 mice (BALB/c background) by interbreeding our TS1 mice with the BALB/c Jh Ϫ/Ϫ line (19). The Jh Ϫ/Ϫ line does not develop mature B cells or produce Ab.…”
Section: Anti-cd45rb-induced Tolerance Requires B Lymphocytesmentioning
confidence: 79%
“…To confirm the generality of this finding, we extended this analysis to the TS1 transgenic model and developed a line of B cell-deficient TS1 mice (BALB/c background) by interbreeding our TS1 mice with the BALB/c Jh Ϫ/Ϫ line (19). The Jh Ϫ/Ϫ line does not develop mature B cells or produce Ab.…”
Section: Anti-cd45rb-induced Tolerance Requires B Lymphocytesmentioning
confidence: 79%
“…Therefore, we crossed AireϪ/Ϫ animals with another line having a more robust block in B cell differentiation. JhϪ/Ϫ mice lack the junctional region of the immunoglobulin (Ig) heavy chain and are thereby incapable of assembling a surface B-cell receptor, leading to a block in B-cell maturation at the pro-B to pre-B-transition (18). We analyzed autoimmunity in AireϪ/ϪJhϪ/Ϫ double-knockout mice, this time on the BALB/c background, compared with AireϪ/Ϫ littermate controls.…”
Section: B Cell Deficiency Protects Aire-null Mice From Their Charactmentioning
confidence: 99%
“…Investigators interested in obtaining mice homozygous for the tgs reported here should contact the Mutant Mouse Regional Resource Center (www.mmrrc.org). All of the mice used in this study, including BALB/c scid/ scid (SCID mice), C57BL/6, (C57BL/6 ϫ BALB/c)F 1 mice, and C.B-17 mice with deleted JH loci (JH Ϫ/Ϫ mice) (25), were raised and maintained behind a barrier as specific pathogen-free mice in the Laboratory Animal Facility of the Fox Chase Cancer Center. Mice were used between 8 and 12 wk of age (unless otherwise stated) according to the protocols approved by the Animal Care and Use Committee of this institution.…”
Section: Micementioning
confidence: 99%